Inferior-Medial Dry Needling at the Thoracolumbar Junction: A Cadaveric Study - Christi L. Williams; Sue E. Curfman; Stacey R. Lindsley; Christian R. Falyar; Ryan C. McConnell (International Journal of Sports Physical Therapy)
# Background